Superintendent Instability in Small Rural Schools: The School Board Perspective - Chance, Edward W.; Capps, James L. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1992)
This study explores the reasons for high turnover within rural superintendencies from the perspective of local boards of education. Forty-one school districts with 600 or fewer students in a southwestern state were identified as experiencing high superintendent turnover (having employed three or more superintendents within the past 5 years). Twenty-five (61 percent of the identified) school board presidents were interviewed over the telephone. The most common problems that existed between the board and previous superintendents included financial mismanagement, financial malfeasance, communication issues, and marital immorality. Twenty-seven (43 percent) of the 63 superintendents who left the districts were either terminated or forced to resign at the end of the school year; 3 (5 percent) were terminated during the school year; 15 (23 percent) resigned to accept positions in larger school districts or positions that paid more; the remainder left because of health reasons or retirement. Ninety-two percent of respondents revealed that only the board interviewed superintendent applicants and most respondents expressed concern about the hiring process. This study suggests: (1) school boards must be more thorough in the selection and hiring process; (2) state agencies responsible for certification of school administrators must become more proactive in addressing the issue of ineffective administrators; (3) the School Boards Association and State Department of Education should monitor and provide direct assistance to those schools experiencing excessive turnover; and (4) educational requirements must be more relevant to issues such as integrity, communication, and morality. (LP)
ERIC Note: Contains some filled-in type.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Selection; Board Administrator Relationship; Boards of Education; Dismissal (Personnel); Elementary Secondary Education; Politics of Education; Rural Education; Rural Schools; School Districts; Small Schools; Superintendents; Tenure; Reports, Research